OPTIMALISASI PEMBINAAN NARAPIDANA PEREMPUAN SEBAGAI UPAYA MENCEGAH TERJADINYA RESIDIVIS DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA SAMARINDA - Tubagus Sukma Wardhana (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACTOne of the things that destroys the community system is the existence of criminals - recurring criminals or what is commonly known as recidivists. These criminals usually repeat the same crimes, even though he has already been sentenced.The type of research that the author uses is empirical juridical research, which is a type of empirical juridical research, or what is called field research, which examines the applicable legal provisions and what happens in reality in society.The results of the study stated that the guidance carried out by the Class II A women's penitentiary Samarinda was not yet effective, but the handling was in accordance with Law Number 12 of 1995 concerning Corrections, which implementation was regulated by Government Regulation No. 31 of 1999 concerning Guidance and Guidance of prisoners and the obstacles faced by the Class II A women's penitentiary Samarinda in an effort to prevent recidivists from occurring are the insufficient number of security officers, the number of assisted residents (residents) that exceeds the capacity, facilities / infrastructure, human resources , marketing the results of limited skills, culture and society, funds, and social and economy. Keywords: Guidance, Prisoners, and Rescue